Slow recoveries through fiscal austerity: New insights in the effects of fiscal austerity - Francesco Bianchi; Diego Comin; Howard Kung; Thilo Kind; Alexander Matusche (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Several European countries such as Spain, Portugal, and Greece implemented austerity programs to cope with the government-debt crisis in the aftermath of the Great Recession: They increased taxes on consumption, labour, and capital and reduced government expenditures to prevent a large increase in the debt-to-GDP ratio. Such policies impose a greater tax burden on the economy which distorts labour supply and investment. We argue that these additional tax distortions make it less attractive for firms to invest in adopting new technologies. New insights from the FRAME project show that fiscal austerity has severe negative consequences for productivity and economic growth in the medium-run and can lead to slow recoveries. Further, austerity may exacerbate existing market failures associated with investment in research and development (R&D) and technology adoption. Beyond its well-known impact on aggregate demand fiscal austerity has a negative effect on future economic growth and productivity growth and hence also on the supply side. Fiscal consolidation is desirable only if it enables a quick reduction of the cost of financing debt but this is unlikely.
Keywords: 330